Burluk – Burluchok: formally unchanged and grammar reframed names (in the basin of Great Burluk river) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The characteristics of interaction of hydronyms Burluk / Burluchok and names of adjacent settlements of toponymic stem Burluk- are studied in the article, the main structural types of hydronyms and oikonyms which become the result of the toponymic metonymy are also analyzed, and the ways of making the names with the original hydronymic lexemes are characterized too.
Keywords: toponym; hydronym; oikonym; toponymic (hydronymic) lexeme; toponymic metonymy